Membaca dan Menulis sebagai Dasar-Dasar Esensial untuk Pembelajaran yang Efektif di Sekolah Dasar - Rizal, Syaiful; Mariatul Qiptiyah, Titin; Husairi, Husairi (STAI Darul Kamal Darul Kamal NW Kembang Kerang, 2025)
Reading and writing skills need to be possessed by students in acquiring knowledge. The most important and primary factor in acquiring knowledge is being skilled in reading and writing. Teachers are required to innovate and be selective in using models, methods and media in the learning process, especially in improving reading and writing skills in elementary school students in the lower grades. The research method uses a literature review. The findings of the researcher found that the learning models that can be used are Cooperative Integrated Reading and Composition (CIRC), Visual, Auditory, Read-Write, Kinesthetic (VARK) and the Edutainment Method, the Edutainment Picture and Picture model. The methods that can be used are the Spell Reading Method, the SAS method (Structural Analytical Synthetic), the child's approach, reading in turns, providing additional hours and cooperation with parents. While the media that can be used are ICT or Power Point, Flashcards, AISEM and MMP modules, Stick letters and smooth upright books